Identification of proteoforms of short open reading frame-encoded peptides in Blautia producta under different cultivation conditions - Jerome Genth; Kathrin Schäfer; Liam Cassidy; Simon Graspeuntner; Jan Rupp; Andreas Tholey (Microbiology Spectrum, 2023)
ABSTRACT Short open reading frames (sORF) have the potential to encode small proteins, sORF-encoded peptides (SEP), which are less than or equal to 100 amino acids in length. These SEP have been associated with various physiological processes and are known for their potential roles in modulating immune responses, signaling pathways, and cellular functions. Using bottom-up and top-down proteomics, we identified 45 novel and formerly reported SEP under different growth conditions and stress exposure in single cultures of Blautia producta that plays a central role in mediating colonization resistance and dampening inflammation in the human gut microbiome. Top-down analysis improved identification confidence and allowed the detection of a number of full-length and N- or C-terminal truncated proteoforms of the SEP and of proteoforms carrying post-translational modifications such as disulfides, which provides hints for a wide functional potential of these molecules. The identification of the SEP in single cultures of this bacterium shows that, in contrast to previous results, the biosynthesis of specific SEP is not restricted to direct bacterial interactions within the microbiome but is dependent on growth and environmental conditions during cultivation. IMPORTANCE The identification of short open reading frame-encoded peptides (SEP) and different proteoforms in single cultures of gut microbes offers new insights into a largely neglected part of the microbial proteome landscape. This is of particular importance as SEP provide various predicted functions, such as acting as antimicrobial peptides, maintaining cell homeostasis under stress conditions, or even contributing to the virulence pattern. They are, thus, taking a poorly understood role in structure and function of microbial networks in the human body. A better understanding of SEP in the context of human health requires a precise understanding of the abundance of SEP both in commensal microbes as well as pathogens. For the gut beneficial B. producta, we demonstrate the importance of specific environmental conditions for biosynthesis of SEP expanding previous findings about their role in microbial interactions.